Development of an Automated Heavy Metal Analyser. Issue 4 (23rd February 2015) - Cases‐Utrera, Joana; Escudé‐Pujol, Roger; Ibáñez‐Otazua, Nora; Javier del Campo, F.; Rees, Neil V.
Abstract This article describes the design, fabrication and characterization of a compact and deployable heavy metal analyzer. The system is autonomous and its microcontroller enables the configuration of its four micropumps and the application of different electroanalytical techniques. A range of prototyping and manufacturing techniques have been used in the fabrication of the instrument, including laser sintering, milling, and laser engraving. We present the electrochemical characterization of the system, and provide preliminary results obtained in the determination of Cu and Zn in different waters. The only sample treatment consists in its 1 : 2 dilution in pH 5.6 acetate buffer. Detection limits of 2.2 and 3.8 ppb were found for Cu and Zn, respectively.